1992
DOI: 10.1530/jrf.0.0940319
|View full text |Cite
|
Sign up to set email alerts
|

Luteal function after intrauterine infusion of recombinant bovine interferon- I1 into postpartum beef cows expected to have short or normal luteal phases

Abstract: Summary. This study was conducted to determine whether intrauterine infusion of recombinant bovine interferon-\g=a\I1(rboIFN-\g=a\I1), which has 70% sequence identity to bovine trophoblast protein-1, will prevent regression of corpora lutea anticipated to have a short lifespan.Twenty-six beef cows in good body condition were allotted to four treatment groups at parturition in a 2 \m=x\ 2 factorial design. Treatments were: group 1, saline; group 2, rboIFN-\g=a\I1;group 3, norgestomet\p=n-\saline; and group 4, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Consistent with this idea, cows destined to have short-lived CL have early secretion of PGF from the uterus (Zollers et al, 1991) and an early increase in circulating metabolite of PGF that begins near the time of the first increases in circulating E2 during the first follicular wave (Southee et al, 1988;Hunter et al, 1989;Cooper et al, 1991;Hunter, 1991;Garverick et al, 1992b). In addition, intrauterine infusion of IFNT, the protein that normally causes maintenance of the CL during pregnancy in ruminants, can prevent short luteal phases (Garverick et al, 1992a). At least part of the action of IFNT is a reduction in uterine secretion of PGF.…”
Section: Period I: Short Luteal Phase and Early CL Regression -Day 5-7mentioning
confidence: 99%
“…Consistent with this idea, cows destined to have short-lived CL have early secretion of PGF from the uterus (Zollers et al, 1991) and an early increase in circulating metabolite of PGF that begins near the time of the first increases in circulating E2 during the first follicular wave (Southee et al, 1988;Hunter et al, 1989;Cooper et al, 1991;Hunter, 1991;Garverick et al, 1992b). In addition, intrauterine infusion of IFNT, the protein that normally causes maintenance of the CL during pregnancy in ruminants, can prevent short luteal phases (Garverick et al, 1992a). At least part of the action of IFNT is a reduction in uterine secretion of PGF.…”
Section: Period I: Short Luteal Phase and Early CL Regression -Day 5-7mentioning
confidence: 99%
“…[24,25]. In sheep, exogenous interferons have been shown to augment conception rates following natural mating [27,28] and to suppress the luteolytic effects of estradiol [29]; and in cattle, exogenous interferons extend the short luteal phase that occurs following the first postpartum ovulation [30].…”
Section: Introductionmentioning
confidence: 99%
“…The more readily available recombinant interferons have been shown to suppress endometrial PGF2a production in vitro in sheep (Salamonsen et al 1988) and cattle (Barros et al 1990). Furthermore, a recent study in post-partum cows showed that intra¬ uterine infusion of recombinant bovine interferon-rxi 1, starting 4-5 days prior to the time of expected premat¬ ure luteolysis, significantly extended luteal lifespan (Garverick et al 1992). In view of the data presented in the current study it is tempting to speculate that the mechanism involves suppression of endometrial oxytocin receptor concentrations.…”
Section: Autoradiographymentioning
confidence: 48%
“…In view of the data presented in the current study it is tempting to speculate that the mechanism involves suppression of endometrial oxytocin receptor concentrations. However, in this and previous studies in this laboratory where ovula¬ tion has been induced in early post-partum ewes, pre¬ mature luteolysis is characterized by very transient progesterone secretion around day 4 of the cycle com¬ pared with the short luteal phase of post-partum cows which varies from 8 to 11 days (Zollers et al 1991 A; Garverick et al 1992). Whether conceptus interferons could similarly rescue the corpus luteum destined to regress prematurely in post-partum ewes is perhaps unlikely but remains to be established.…”
Section: Autoradiographymentioning
confidence: 64%